China’s Strategy for Free Trade Agreements: Political Battle in the Name of Trade - GAO, Shuchao Henry (Institutional Knowledge at Singapore Management University, 2009)
Compared with Europe and America, East Asia is a latecomer in the new gold-rush of Free Trade Agreements (FTAs). In this process, China has played a significant role. This is not only due to the growing economic clout of China, but also because China has taken a conscious strategy to push for economic integration in the region. Thus, for the benefits of the countries in the region, it is very important to understand China’s FTA strategy. This article starts with the evolving picture of China’s FTA web, then discusses the key components of China’s FTA strategy, and concludes by noting the implications of China’s FTA strategy on the region and beyond.